Exploring the Outcomes and Obstacles of University Entrepreneurship Education: Evidence from Scientific Literature - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernàndez-Bedoya, Víctor Hugo; Alvarado-Suyo, Sofía Almendra; Ocupa-Cabrera, Hitler Giovanni (LACCEI, 2023)
The university plays a pivotal role not only in students’ academic development but also in enhancing their skills to tackle challenges. Entrepreneurship education enables the transformation of difficulties into opportunities, paving the way for success. The aim of this study was to systematically compile scientific evidence concerning the outcomes and challenges of entrepreneurship education within university classrooms. The search was conducted across SciELO, Scopus, and Web of Science databases, utilizing a search equation composed of synonyms and Boolean operators AND and OR. Inclusion and exclusion criteria were established, resulting in the selection of 20 scholarly articles that aligned with the outlined objective. Following analysis, four key aspects emerged: personal and cultural barriers, entrepreneurial knowledge, government-related obstacles, and misconceptions about entrepreneurship as a career path. The research concludes that entrepreneurship within universities reflects a global acknowledgment of its significance in shaping future innovative leaders